MACROZOOBENTHOS DIVERSITY AS A BIOINDICATOR OF WATER QUALITY AROUND THE CENTER POINT OF INDONESIA (CPI) - Rahman, Fathin Nur; Tambaru, Rahmadi; Lanuru, Mahatma; Lanafie, Yayu A; Samawi, Muh. Farid (Jurnal Ilmu Kelautan SPERMONDE, 2023)
Benthos are invertebrate animals that live at the bottom of the waters. One biota that can be used as a biological parameter in determining the quality of a waters is macrozoobenthos. The waters around the Center Point of Indonesia (CPI) are one of the waters that have received a lot of additional organic matter and other pollutant materials through the estuaries of the canals that flow into the waters of Losari Beach. The study was conducted by sampling macrozoobenthos at each station using Ejkman Grab at each station 3 times sampling then sieved using a benthos sieve measuring 1 mm. In addition, measurements of environmental factors were carried out at each station with 3 replications directly in the field and analyzed in the laboratory. The results of the macrozoobenthos sampling study obtained 4 macrozoobenthos classes found at the study site, namely the Gastropod Class (4 species), the Crustacea Class, the Ophiuroidea Class, and the Oligochaeta Class each 1 species. The highest diversity and abundance of macrozoobenthos was found at Station 6 which is suspected because this station has a sandy sediment texture and sediment DOM content and high concentrations of water solubility of oxygen which support the life of makzoobenthos. Macrozoobenthos diversity at the study site (waters around the Center Point of Indonesia) is low with a diversity index (H') value of 0.00 - 0.16. The high abundance of makzoobenthos at Station 5 and Station 6 is characterized by high current velocity, sediment DOM and high oxygen concentration.